STUDI PENGUKURAN BRAND IDENTITY DALAM MENINGKATKAN KUNJUNGAN WISATA BUKIT CINTA RAWA PENING KABUPATEN SEMARANG - Asha Eilena Khairunisa; Amni Zarkasyi Rahman; Retno Sunu Astuti (Journal of Public Policy and Management Review, 2023)
Tourist visits to the Bukit Cinta Rawa Pening tourist attraction have not been optimal. This study aims to determine the strengthening of brand identity to increase tourist visits to Bukit Cinta Rawa Pening and to analyze the driving and inhibiting factors. This study uses the Analytical Hierarchy Process (AHP) method with a quantitative approach to obtain decisions regarding branding strengthening strategies. The results of the study shows that Branding has been strengthened on 4 tourism components (4A), with priority on the Attraction aspect with a total score of 0.35. The driving factors include; the supporting natural and cultural attractions, the supporting basic and additional facilities, the strategic location with adequate road infrastructure, the availability of active online promotional media, and collaboration with various parties in order to increase tourist visits. The inhibiting factors include; the growth of water hyacinth which disturbs the beauty of nature, limited tourism management related to conservation rules by BBWS, limited budget management, lack of variety of water tourism, no restaurants within the tourist attraction area, the little number of public transportations around the tourist object, and the use of online promotional media is not yet optimal. Suggestions that can be given are; Managers and local governments need to make efforts to maintain the beauty and sustainability of Lake Rawa Pening, as well as optimizing online promotional media. It is necessary to increase capacity building for the managers and staff of Bukit Cinta Rawa Pening.